Review of performance of trained TBAs - Akhtar, Halida Hanum; Bangladesh Institute of Research for Promotion of Essential & Reproductive Health and Technologies (Dhaka, Bangladesh : Bangladesh Institute of Research for Promotion of Essential &Reproductive Health and Technologies, 1995)
With reference to Bangladesh.
Keywords: Midwives -- Bangladesh; Abortion -- Bangladesh -- Bibliography; Maternal health services -- Bangladesh